2020
DOI: 10.1002/jor.24949
|View full text |Cite
|
Sign up to set email alerts
|

Single‐stage revision of MRSA orthopedic device‐related infection in sheep with an antibiotic‐loaded hydrogel

Abstract: Local antimicrobial therapy is an integral aspect of treating orthopedic devicerelated infection (ODRI), which is conventionally administered via polymethylmethacrylate (PMMA) bone cement. PMMA, however, is limited by a suboptimal antibiotic release profile and a lack of biodegradability. In this study, we compare the efficacy of PMMA versus an antibiotic-loaded hydrogel in a single-stage revision for chronic methicillin-resistant Staphylococcus aureus (MRSA) ODRI in sheep. Antibiofilm activity of the antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…Moreover, previous studies revealed that a locally applied antibiotic-loaded carrier (biodegradable or non-biodegradable) would not increase the systemic concentration of the drugs. 31 , 42 In our study, the concentration of the applied antimicrobial agents remained above the MIC90, yet localized, without systemic spreading. Compared with other delivery agents, the tunable porosity and pore size of nanofibers permit them to mimic the extracellular matrix (ECM) to enhance cell proliferation.…”
Section: Discussionsupporting
confidence: 45%
“…Moreover, previous studies revealed that a locally applied antibiotic-loaded carrier (biodegradable or non-biodegradable) would not increase the systemic concentration of the drugs. 31 , 42 In our study, the concentration of the applied antimicrobial agents remained above the MIC90, yet localized, without systemic spreading. Compared with other delivery agents, the tunable porosity and pore size of nanofibers permit them to mimic the extracellular matrix (ECM) to enhance cell proliferation.…”
Section: Discussionsupporting
confidence: 45%
“…A group of the AO Research Institute, Davos, Switzerland, published two laborious studies using sheep infection models to test the efficacy of a gentamicin and vancomycin-loaded hydrogel. One study described the effect of a single-stage revision [ 28 ], while in the other study, a two-stage model was used [ 29 ]. Both studies used poly(N-isopropylacrylamide)-grafted thermoresponsive hyaluronic acid hydrogel loaded with gentamicin and vancomycin and systemic antibiotic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For example, when treating fracture or implantrelated bone infections, a higher stiffness is typically desired to provide mechanical stability. [30] Therefore, the possibility to regulate the mechanical properties of the PMB-triggered PA hydrogels was exploited here to expand their potential applications. Even though tunable stiffness of the PMB-triggered PA hydrogel could be obtained by adjusting the concentration of TPA, the variation range is narrow with the highest G′ obtained under 10 kPa (Figure 4b).…”
Section: Tunable Mechanical Propertiesmentioning
confidence: 99%